Normalizing the Use of Single-Item Measures: Validation of the Single-Item Compendium for Organizational Psychology - Matthews, Russell A.; Pineault, Laura; Hong, Yeong-Hyun (Journal of business and psychology, 2022)
The application of single-item measures has the potential to help applied researchers address conceptual, methodological, and empirical challenges. Based on a large-scale evidence-based approach, we empirically examined the degree to which various constructs in the organizational sciences can be reliably and validly assessed with a single item. In study 1 , across 91 selected constructs, 71.4% of the single-item measures demonstrated strong if not very strong definitional correspondence (as a measure of content validity). In study 2 , based on a heterogeneous sample of working adults, we demonstrate that the majority of single-item measures examined demonstrated little to no comprehension or usability concerns. Study 3 provides evidence for the reliability of the proposed single-item measures based on test–retest reliabilities across the three temporal conditions (1 day, 2 weeks, 1 month). In study 4 , we examined issues of construct and criterion validity using a multi-trait, multi-method approach. Collectively, 75 of the 91 focal measures demonstrated very good or extensive validity, evidencing moderate to high content validity, no usability concerns, moderate to high test–retest reliability, and extensive criterion validity. Finally, in study 5 , we empirically examined the argument that only conceptually narrow constructs can be reliably and validly assessed with single-item measures. Results suggest that there is no relationship between subject matter expert evaluations of construct breadth and reliability and validity evidence collected across the first four studies. Beyond providing an off-the-shelf compendium of validated single-item measures, we abstract our validation steps providing a roadmap to replicate and build upon. Limitations and future directions are discussed.